ROLE OF INDIGENOUS KNOWLEDGE IN MANAGING FLOODS PROJECTS - AHMAD, MUSHTAQ (Advances in Social Sciences Research Journal, 2019)
Climate change is increasing the frequency of disasters in the world. Accordingly, disaster management strategies are also changing. The UN has focused on acknowledging the Indigenous Knowledge in disaster management strategies. In this study, the village Khursheed in District Sargodha has been focused due to facing frequent floods since decades. They have developed some methods to counter floods. The study was qualitative containing three focus group discussions and thirty interviews, reveals that villagers have devised their own flood forecast and early warning systems. The indigenous methods of constructions of buildings and agricultural techniques have rendered the village more resilient. The elevated spiritual level has enhanced their immune system to face floods. The government needs to devise local level disaster management strategies which should incorporate indigenous and modern knowledge.